Alterations in brain network functional connectivity and topological properties in DRE patients - Ding, Yongqiang; Guo, Kunlin; Li, Jialiang; Shan, Qiao; Guo, Yongkun; Chen, Mingming; Wu, Yuehui; Wang, Xinjun (Frontiers in Neurology, 2023)
The study aim was to find the difference of functional network topology on inter-ictal electroencephalographic(EEG) between patients with drug-resistant epilepsy(DRE) and healthy people.We retrospectively analyzed the medical records as well as EEG data of ten patients with DRE and recruited five sex-age matched healthy controls ( HC group). Each participant remained awake while undergoing video-electroencephalography (vEEG)monitoring. After excluding data that contained abnormal discharges, we screened EEG segments that were free of artifacts and put them together into 20-minute segments. The screened data was bandpass filtered to different frequency bands (delta, theta, alpha, beta, gamma). The weighted phase lag index (wPLI) and the network properties were calculated to evaluate changes in the topology of the functional network.Finally, the results were statistically analyzed and the false discovery rate (FDR) was used to correct for differences after multiple comparisons.In the full frequency band (0.5-45Hz), the functional connectivity in the DRE group during the inter-ictal period was significantly lower than that in the HC group (P < 0.05). Compared to the HC group, in the full frequency band, the DRE group exhibited significantly decreased clustering coefficient (CC), node degree (D), and global efficiency (GE), while the characteristic path length (CPL) significantly increased (P < 0.05). In the sub-frequency bands, the functional connectivity of the DRE group was significantly lower than that of the HC group in the delta band but higher in the alpha, beta, and gamma bands (P < 0.05). The statistical results of network properties revealed that in the delta band, the DRE group had significantly decreased values for D, CC, and GE, but in the alpha, beta, and gamma bands, these values were significantly increased (P < 0.05). Additionally, the CPL of the DRE group significantly increased in the delta and theta bands but significantly decreased in the alpha, beta, and gamma bands (P < 0.05).The topology structure of functional network in DRE patients was significantly changed compared with healthy people, which was reflected in different frequency bands. It provided a theoretical basis for understanding the pathological network alterations of DRE.